Europejskie dylematy ukraińskich wyborów - Muszkiewicz, Marian (European dilemmas of Ukraine's choices, 2007)
Ukraine gained full independence in 1990 as a consequence of the disintegration of the U.S.S.R. It is the second biggest European country after Russia (603 700 km2) with the population of nearly 47 million. What has a bearing on the future of the country, is the remnants of its past, the present social and economic situation, its particular relationship with Russia, as well as the geopolitics of its location, bordering with the European Union. From the perspective of the European Union, Ukraine is an important political partner. However, it does not seem likely that it should be invited to become a member of the Union within the next few years. Today, Ukraine faces a choice: rapprochement with the West on the basis of constant, ambitious reforms - social, political, and economic, or continuation of the present, “multisection” policy which calms down the tensions, but does not define the prospects for the future.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (11); 2007; nr 1188, s. 80-96